Tuboovarian Abscesses in Postmenopausal Women - Sheng-Mou Hsiao; Fon-Jou Hsieh; Yih-Ron Lien (Elsevier, 2006)
Objective: To compare the clinical features of tuboovarian abscess (TOA) in pre- and postmenopausal women. Materials and Methods: Between January 1992 and December 2000, all patients with surgically documented TOA at National Taiwan University Hospital were enrolled into this retrospective study. Salient information with respect to the history, current illnesses, risk factors, physical findings, laboratory data, surgeries and postoperative complications was obtained from medical records. Results: Of 74 patients with TOA, nine were postmenopausal women. Compared with the premenopausal group, postmenopausal patients were significantly more likely to have contributing medical disorders (p < 0.001) and concomitant pelvic malignant tumors (p = 0.037). Conclusion: Thorough investigation for concomitant pelvic malignant tumors and meticulous medical care should be provided for postmenopausal women with TOA.